Análise paramétrica da estabilidade de falésias e estudo de caso da Ponta do Pirambu em Tibau do Sul/RN - Ribeiro, João Ronyberto Cavalcante (2015)
The coastline from Rio Grande do Norte state is characterized for the presence of dunes and cliffs. The latter consist of slopes with height up to 40 meters and inclinations ranging from 30° to 90° wich horizontal. Thus, this dissertation had as objective the evaluation of the stability of cliff from Ponta do Pirambu in Tibau do Sul/RN, and the realization of a parametric study on the stability of a homogeneous cliff considering as variables the material's cohesion, the cliff height and the slope inclination. The study in Ponta do Pirambu considered yet the possibility of the existence of a colluvial cover with thickness ranging from 0.50 to 5.00 meters. The analyzes were performed by Bishop method, using GEO5 software. In parametric analysis were produced graphics that relate height cliff with the inclination, to safety factors equals to 1.00 and 1.50; besides graphics where it is possible easily get the lowest safety factor as from the cohesion, cliff height and its inclination. It was concluded that these graphs are very useful to preliminary analyzes, for the definition of critical areas in risk mappings in areas of cliffs and for determination of an equation for obtaining the lowest safety factor function of the strength parameters and of slope geometry. Regarding the cliff from Ponta do Pirambu, the results showed that the cliff is subject to superficial landslides located in the points where may there be the presence of colluvium with thicknesses greater than two meters. However, the cliff remains stable presenting the global safety factor equal or superior to 2.50 in the saturated condition.